Electrochemical performance of facile developed aqueous asymmetric (Fe, Cr)2O3//MnO2 supercapacitor. (20th September 2018) - Deshmukh, P.R.; Sohn, Youngku; Shin, Weon Gyu
Abstract: The present study demonstrate the development of novel aqueous asymmetric supercapacitor based on polygonal integrated oxide layer ((Fe, Cr)2 O3 ) as the anode and spherical MnO2 nanoparticles as the cathode. The polygonal (Fe, Cr)2 O3 integrated oxide layer was obtained by the simple thermal oxidation method and low-cost, scalable chemical route was employed for the synthesis of spherical MnO2 nanoparticles. Furthermore, electrochemical investigations of asymmetric supercapacitor (ASC) studied in aqueous electrolytes show an extended operating voltage of 1.6 and 2.0 V with the maximum specific capacitance of 34 and 37 Fg -1 in KOH and Na2 SO4, respectively. The observed energy density and power density of ASC in Na2 SO4 (or KOH) electrolyte is 20.89 (or 12.36) Whkg −1 and 2173.913 (or 1739) Wkg −1, respectively. ASC shows the better capacitance retention over the 5000 cycles in both the electrolytes. Therefore, present study open-up new construction of inexpensive petty (Fe, Cr)2 O3 anode material for the development of high energy density ASCs. Graphical abstract: Image 1 Highlights: Preparation of (Fe, Cr)2 O3 oxide layer and MnO2 nanoparticles as a binder free electrode materials. (Fe, Cr)2 O3 and MnO2 shows the specific capacitance of 372 and 174 Fg -1 in Na2 SO4 electrolyte. Development of aqueous asymmetric supercapacitor made from (Fe, Cr)2 O3 and MnO2 . Asymmetric supercapacitor shows the high specific capacitance of 37 Fg -1 in Na2 SO4 electrolyte. Asymmetric supercapacitor shows the high-energy density of 20.89 Whkg −1 in Na2 SO4 electrolyte.